Bibliometric Analysis of Sports and Gender Equality Studies in the Context of Sustainable Development Goals - Caliskan, Kadir; Engin, Sabiha Gizem (European Journal of Sustainable Development, 2025)
Academic studies indicate that the topic of sport and sustainability is increasingly taking a prominent role in social life and is accepted as a societal norm, since sustainable development efforts play a crucial role in enhancing social well-being, promoting gender-inclusive participation, and empowering women. Accordingly, examining research trends on these topics over time constitutes an important area of study. This study investigates the growing number of scientific publications on gender equality in sport, produced within the framework of the SDGs and published between 1992 and 2025, through a bibliometric analysis. A total of 801 research records were obtained from the Web of Science Core Collection and analysed with VOSviewer, focusing on productivity and collaboration networks across authors, universities, countries, and publishers. The findings highlight the dominance of the United States, followed by the United Kingdom, Australia, and Canada, and show that research has gained momentum since the 1990s, with a marked increase particularly after the United Nations announced the SDG vision in 2015. Moreover, the results reveal that conceptual focuses in the field of sport and gender equality have diversified, with themes such as “inclusivity” and “feminism” gaining prominence. By identifying gaps in the literature, this study offers strategic opportunities for emerging researchers and contributes to a deeper understanding of the role of sport in advancing gender equality goals within sustainable development. Keywords: bibliometric analysis, sports studies, sustainability, gender equality, SDGs